The Luxembourg Declaration on Patient Safety: a political comment (Italian Journal of Public Health, 2005)
Services provided for European citizens’ healthcare are not services like standard commercial services. Healthcare services need to be accessible, independent of the citizen’s economic or social background and should at the same time be available to all at the best possible quality level.The Luxembourg Declaration on Patient Safety recognizes these challenging fundamental principles. Patient safety is a key aspect for all European policy makers, as it is a vital question of equitable access to health care. Nevertheless we know that unfortunately a considerable amount of avoidable safety events still occur all across Europe!However differently organized our national health systems may be, it is vital to share experience and knowledge at a European level in order to be able to learn from the experiences of the different memberstates. No uniform solution can be found and decreed from the bottom down, nevertheless Europe can contribute and help to raise standards by a common effort. The Luxembourg Declaration is a launching pad for European progress in this field as it sets important goals and demonstrates the steps to be undertaken. It is a calling and gives us hope for measurable progress in the future.
Keywords: Patient safety; Europe